Balkan dialogues: negotiating identity between prehistory and the present - Gori, Maja; Ivanova-Bieg, Maria (Routledge studies in archaeology, 2017)
"Spatial variation and patterning in the distribution of artefacts are topics of fundamental significance in Balkan archaeology. For decades, archaeologists have classified spatial clusters of artefacts into discrete 'cultures,' which have been conventionally treated as bound entities and equated with past social or ethnic groups. This timely volume fulfils the need for an up-to-date and theoretically informed dialogue on group identity in Balkan prehistory. Thirteen case studies covering the beginning of the Neolithic to the Middle Bronze Age and written by archaeologists conducting fieldwork in the region, as well as by ethnologists with a research focus on material culture and identity, provide a robust foundation for exploring these issues. Bringing together the latest research, with a particular intentional focus on the central and western Balkans, this collection offers original perspectives on Balkan prehistory with relevance to the neighbouring regions of Eastern and Central Europe, the Mediterranean and Anatolia. Balkan Dialogues challenges long-established interpretations in the field and provides a new, contextualised reading of the archaeological record of this region"--Provided by publisher
"This volume stems from the international conference 'Balkan Dialogues: Spatial Boundaries and Cultural Identities in the Prehistoric Balkans', held on 2-3 May 2014 at Internationales Wissenschaftsforum, Univeristy of Heidelberg." (Seite 11)
Includes bibliographical references and index
Keywords: Balkan Peninsula -- Antiquities; Balkan Peninsula -- Social life and customs; Aufsatzsammlung; Konferenzschrift -- 02.05.2014-03.05.2014 -- Heidelberg; Bronzezeit; Neolithikum; Funde; Siedlung; Archäologie; Balkanhalbinsel; Ethnologie